2018
DOI: 10.1503/cjs.007417
|View full text |Cite
|
Sign up to set email alerts
|

Beyond just the operating room: characterizing the complete caseload of a tertiary acute care surgery service

Abstract: Acute care surgery teams care for a wide breadth of disease, a considerable amount of which is managed nonoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The complete caseload of ACS services extends beyond these 2 common presentations, however, and therefore studies examining the other patients managed by EGS surgeons are essential to provide a framework for understanding the epidemiology, morbidity and mortality associated with nonbiliary, nonappendiceal conditions. [8][9][10] These studies demonstrate operative rates in admitted patients ranging from 25% to 88%. 3,[8][9][10] In all series, the most frequently performed operations are appendectomy and cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete caseload of ACS services extends beyond these 2 common presentations, however, and therefore studies examining the other patients managed by EGS surgeons are essential to provide a framework for understanding the epidemiology, morbidity and mortality associated with nonbiliary, nonappendiceal conditions. [8][9][10] These studies demonstrate operative rates in admitted patients ranging from 25% to 88%. 3,[8][9][10] In all series, the most frequently performed operations are appendectomy and cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] These studies demonstrate operative rates in admitted patients ranging from 25% to 88%. 3,[8][9][10] In all series, the most frequently performed operations are appendectomy and cholecystectomy. Similar to our results, however, the remainder of the cases can be categorized as hernia repairs, bowel resections for benign and malignant disease, and drainage of skin and soft tissue infections.…”
Section: Discussionmentioning
confidence: 99%
“…Where dedicated EGS teams are provided access to daytime OR resources, the ACS model has the potential to address this issue. 35 A recent meta-analysis by Murphy and colleagues found that the benefits of the ACS model are dependent on access to dedicated daytime OR resources. 9 Unfortunately, this remains a major challenge for most Canadian institutions.…”
Section: Discussionmentioning
confidence: 99%
“… 42 Although comparative Canadian data are lacking, data from the ACS service in London, Ontario, indicated an average case volume of 14 cases per week, although logs of actual resident-attended operations were not reported. 35 Resident case log data from American training programs indicated that residents attended approximately 9 cases per week. 19 Overall, the case volume reported by McMaster University general surgery residents is low, which raises concerns about the adequacy of their exposure to EGS operations while they are on ACS rotations.…”
Section: Discussionmentioning
confidence: 99%
“…Much of this work is being championed by the Canadian Collaborative on Urgent Care Surgery (CANUCS). 15,23,[29][30][31] Direction for future studies, particu larly at centres introducing physician extenders on their ACS service (PAs, NPs, hospitalists), include objective assessment of the impact on ACS service efficiency and costeffectiveness, patient outcomes, emergency depart ment disposition times, resident learning, and satisfaction scores for residents, staff and allied health team members. These outcomes should be tracked and collected by a research team member rather than the already overbur dened ACS team members (PA, residents, etc.…”
Section: Discussionmentioning
confidence: 99%